Immunohistochemical TTF-1 and Napsin a Expression in Gastrointestinal Adenocarcinomas—Low Frequency but an Important Pitfall - Petar Noack; Claudia Grosse; Simon Eschemann; Bastian Dislich; Rupert Langer (Diagnostics, 2025)
Background/Objectives: TTF-1 and Napsin A are immunohistochemical markers that are widely used for the diagnosis of lung adenocarcinomas or thyroid carcinomas, as well as the characterization of metastases. However, several publications have reported the aberrant expression of one or both markers in extrathoracic malignancies, including gastrointestinal adenocarcinomas. The goal of our study was to determine the frequency of TTF-1- and Napsin A-positive neoplasms in cohorts consisting of esophageal, gastric and colorectal adenocarcinomas. Methods: Buffered formalin-fixed paraffin-embedded tumor tissues from 854 patients with primary resected gastrointestinal and esophageal carcinomas were placed in tissue microarrays (TMAs) for investigation. Between two and six tumor cores were analyzed for each case. For immunohistochemical staining, we used TTF-1 (SPT24 clone) and Napsin A (IP64 clone). Tumors were considered positive if at least 5% of their tumor cells showed weak nuclear (TTF-1) or cytoplasmic (Napsin A) staining. Results: In total, 16 cases showed positive staining for TTF-1, alongside 7 cases for Napsin A. The greatest proportion of TTF-1- and/or Napsin A-positive tumors was found among esophageal adenocarcinomas (5/125 cases; 4%). Co-expression of TTF-1 and Napsin A was found in five cases, including three esophageal and two gastric adenocarcinomas. In colorectal carcinomas, co-expression of these markers was not detected. Conclusions: TTF-1 and Napsin A are useful immunohistochemical makers for establishing the diagnosis of pulmonary adenocarcinoma. Additionally, knowing that a proportion of gastrointestinal neoplasms express these markers can help to avoid diagnostic misinterpretations.